Descending Necrotizing Mediastinitis: Current Strategies for Diagnosis and Treatment - K. Freeman, Richard; Giannini, Theresa; Vyverberg, Amy; J. Ascioti, Anthony (Current Respiratory Medicine Reviews, 2012)
Descending necrotizing mediastinitis is an acute, polymicrobial infection. Originating in the pharynx or neck, this necrotizing process descends into the chest producing widespread tissue necrosis. Despite the introduction of modern antimicrobial therapy and computed tomographic imaging, this form of mediastinitis has continued to produce reported mortality rates of 25% to 40%. This review discusses the pathophysiology, diagnosis and treatment of descending necrotizing mediastinitis with recommendations for treating physicians based on the modern literature.
Keywords: Descending